Photorefractive optics : materials, properties, and applications - Yin, Shizhuo, 1963-; Yu, Francis T. S., 1932- (Academic, 2000)
The advances of photorefractive optics have demonstrated many useful and practical applications, which include the development of photorefractive optic devices for computer communication needs. To name a couple significant applications: the large capacity optical memory, which can greatly improve the accessible high-speed CD-ROM and the dynamic photorefractive gratings, which can be used for all-optic switches for high-speed fiber optic networks. This book is an important reference both for technical and non-technical staffs who are interested in this field. * Covers the recent development in materials, phenomena, and applications * Includes growth, characterization, dynamic gratings, and liquid crystal PR effect * Includes applications to photonic devices such as large capacity optical memory, 3-D interconnections, and dynamic holograms * Provides the recent overall picture of current trends in photorefractive optics * Includes optical and electronic properties of the materials as applied to dynamic photorefractive fiber.